Assessment of the dimensions of organizational health in the branch of Damascus university in Quneitra (Damascus University Journal for the economic and Political sciences, 2025)
This study aimed to assessment the dimensions of organizational health in the branch of the Damascus University in Quneitra, where these dimensions are represented by ((participation and contribution – commitment – ​​reputation or organizational integrity – trust))This study was applied in the faculties of the Damascus University branch in Quneitra, represented by three faculties (the third Faculty of Economics - the fourth Faculty of Education - the third Faculty of Law).A sample of (86) workers in this college was selected with their various job titles (professors - administrators - workers).The researcher used the questionnaire, the study tool, to collect data, and this study reached the most important results: the level of importance of each of the dimensions of organizational reputation -trust-commitment was low due to the weakness of management in performing its tasks towards its employees While the level of importance after participation was medium because of social relations as far as the researcher knows.
Keywords: Organizational Health; Trust; Reputation Or Organizational Integrity; Contribution; Commitment